A comprehensive examination of indicators for evaluating poverty and social exclusion - Vasja Roblek; Anamarija Kejžar (Discover Global Society, 2025)
Abstract Growing inequality in the distribution of wealth means there is today a greater need for effective social policies to combat poverty and social exclusion. The use of comprehensive indicators to monitor and evaluating the implementation of social policies is crucial for addressing these challenges. Social exclusion is a multifaceted phenomenon linked to poverty, often exacerbated by factors like unemployment, discrimination and a lack of basic services. It can be the cause—or consequence—of poverty. Tackling these problems requires a holistic approach involving indicators to assess material deprivation, unemployment, and access to basic services.